Urban religion in Roman Corinth : interdisciplinary approaches - Schowalter, Daniel N., 1957-; Friesen, Steven J. (Cambridge, Mass. : Harvard Theological Studies, Harvard Divinity School, 2005)
"Seventeen essays on the history, archaeology, urban development, and religious practices of ancient Corinth, with special attention to the early history of Christianity. Topics include burial customs, water supply, city planning, and sociology. Results of an interdisciplinary conference held at Harvard University, January 2002--Provided by publisher.
Urban Corinth : an introduction / G.D.R. Sanders -- Urban and rural planning in Roman Corinth / David Gilman Romano -- Favorinus's "Corinthian oration" : a piqued panorama of the hadrianic forum / L. Michael White -- Fountains and the formation of cultural identity at Roman Corinth / Betsey A. Robinson -- Religion in Corinth : 146 B.C.E. to 100 C.E. / Nancy Bookidis -- Rites for Melikertes-Palaimon in the early Roman Corinthia / Elizabeth R. Gebhard -- The stones don't speak and the texts tell lies : sacred sex at Corinth / John R. Lanci -- Roman Corinth : the final years of pagan cult facilities along East Theater Street / Charles K. Williams II -- Unquiet graves : burial practices of the Roman Corinthians / Mary E. Hoskins Walbank -- Placing the dead : funerary practice and social stratification in the early Roman period at Corinth and Ephesos / Christine M. Thomas -- Paul's letters to Corinth : the interpretive intertwining of literary and historical reconstruction / Margaret M. Mitchell -- The silence of the apostle / Helmut Koester -- Prospects for a demography of the Pauline mission : Corinth among the churches / Steven J. Friesen -- Paul's assembly in Corinth : an alternative society / Richard A. Horsley -- Identity in Roman Corinth and its impact on early Christians / James Walters -- Archaeological evidence for early Christianity and the end of hellenistic religion in Corinth / G.D.R. Sanders -- Ecclesiastical ambiguities : Corinth in the fourth and fifth centuries / Vasiliki Limberis.
Includes bibliographical references (p. [459]-498) and indexes.
Keywords: Christianity and other religions -- Greek; Church history -- Primitive and early church, ca. 30-600.; Corinth (Greece) -- Religion; Corinth (Greece) -- Antiquities; Corinth (Greece) -- Church history